“Influencia de las características sociodemográficas en la depresión posparto en Puérperas atendidas en el Hospital II ESSALUD Tarapoto y Hospital Minsa II - 2 Tarapoto. Setiembre 2015 - Enero 2016” - Vera Mendoza, Jhudit (2016)
This study entitled "Influence of socio-demographic characteristics in postpartum Depression in postpartum women treated at the Hospital II essalud and MINSA Tarapoto Tarapoto II-2 Hospital. September 2015 - January 2016 "quantitative, Descriptive, correlational study, whose sample consisted of 95 puerperal MINSA and Essalud 54. The results were: 37% of users essalud range from 31 to 40 years and 33.7% Between 26-30 years of the MOH; 74.1% and 72.6% are cohabiting; 59.3% and 64.2% were housewife; 31.5% and 30.5% had completed secondary school. According to monthly household income 46.3% from 1.201 to 1.600 soles and 58.9% from 501 to 800; main contributor spouse 70.4% vs 64.3%, respectively. 44.4% and 40.3% live in Tarapoto; 77.8% and 85.2% own their homes; 92.6% and 91.3% receive support from family care of your health and your baby. The type of Nuclear family is composed 92.6% vs 90.5%. 14.8% and 12.6% were abused by a Spouse 91.7%. Sexual violence was the most frequent 62.5% and 41.7%. The Proportion of postpartum depression is 44.4% (24) in essalud and 58.9% (56) in MOH. Social characteristics: level of education of the couple (p = 0.0360000) and Occupation of the pair (p = 0.0180000), significantly influence the presence of Postpartum depression in postpartum women treated at the Hospital II-2 Tarapoto. Conclusion: There is significant influence between social characteristics and Postpartum depression in new mothers attended at two health facilities: where you Live (p = 0.0500000), housing tenure (p = 0.0270000), level of education the pair (p = 0.0320000) and occupation of the pair (p = 0.0340000).